Facilitators and barriers to HIV pre-exposure prophylaxis (PrEP) uptake through a community-based intervention strategy among adolescent girls and young women in Seme Sub-County, Kisumu, Kenya - Maya Jackson-Gibson; Ashley Uzoamaka Ezema; Wicklife Orero; Irene Were; Ramael Osasogie Ohiomoba; Patrick Owuor Mbullo; Lisa Ruth Hirschhorn (BMC, 2021)
Abstract Background While the introduction of HIV Pre-Exposure Prophylaxis (PrEP) as an HIV prevention strategy has allowed women to exercise more control over the reduction of HIV transmission rates, adolescent girls and young women in Sub-Saharan Africa continue to experience higher rates of HIV infections and bear the greatest disease burden. Understanding progress in PrEP uptake among adolescent girls and young women would enhance risk reduction in this vulnerable population. The Determined, Resilient, AIDS-Free, Mentored and Safe women (DREAMS) Initiative plays a key role in this risk reduction strategy. Methods We performed a qualitative study to explore facilitators and barriers to PrEP implementation and assess factors effecting initiation and persistence on PrEP among adolescent girls and young women enrolled in the DREAMS Initiative at Pamoja Community Based Organization in Kisumu, Kenya. We conducted key informant interviews (n = 15) with Pamoja Community Based Organization staff, health care providers and community leaders. Additionally, we conducted focus group discussions with young women receiving PrEP and peer mentors (n = 40). We performed a directed content analysis using the Consolidated Framework for Implementation Research to organize the identified facilitators and barriers. Results We found that the use of the safe space model, decentralization of PrEP support and delivery, peer mentors, effective linkage to local health care facilities, the sensitization of parents and male sexual partners, disclosure of PrEP use by beneficiaries, active stakeholder involvement and community engagement were among some of the facilitators to PrEP uptake. Barriers to PrEP implementation, initiation and persistence included stigma associated with the use of anti-retroviral drugs, drug side effects, frequent relocation of beneficiaries, limited resources for routine screening and medication monitoring, and a limited number of qualified health care workers for PrEP distribution and administration. Conclusion Overall, the community roll-out of PrEP within the DREAMS Initiative was successful due to a number of key facilitating factors, which ultimately led to successful PrEP implementation, increased PrEP initiation and enhanced persistence among adolescent girls and young women. The identified barriers should be addressed so that a larger scale-up of PrEP roll-out is possible in the future.